2021
DOI: 10.1302/2058-5241.6.200064
|View full text |Cite
|
Sign up to set email alerts
|

Modular neck stems in total hip arthroplasty: current concepts

Abstract: Modular neck (MN) implants can restore the anatomy, especially in deformed hips such as sequelae of development dysplasia. Early designs for MN implants had problems with neck fractures and adverse local tissue, so their use was restricted to limited indications. Results of the latest generation of MN prostheses seem to demonstrate that these problems have been at least mitigated. Given the results of the studies presented in this review, surgeons might consider MN total hip arthroplasty (THA) for a narrower p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…However, the outcomes of the present report are quite reassuring about neck breakage. Once again, the heavier men demonstrated to be unsuitable candidates for modularity due to the higher risk of neck breakage, as unanimously reported in the literature [5,6,17,18]. While no differences were noted in large cohorts, modular implants may still provide some additional benefits even in cases with primary osteoarthritis.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, the outcomes of the present report are quite reassuring about neck breakage. Once again, the heavier men demonstrated to be unsuitable candidates for modularity due to the higher risk of neck breakage, as unanimously reported in the literature [5,6,17,18]. While no differences were noted in large cohorts, modular implants may still provide some additional benefits even in cases with primary osteoarthritis.…”
Section: Discussionmentioning
confidence: 68%
“…However, the outcomes of the present report are quite reassuring about neck breakage. Once again, the heavier men demonstrated to be unsuitable candidates for modularity due to the higher risk of neck breakage, as unanimously reported in the literature [ 5 , 6 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This may be due to the relatively small number of Co-Cr necks (42.7%) used in the present series. It has been previously reported that Co-Cr modular necks in combination with Ti6Al4Ti femoral stems fracture earlier than Ti6Al4Ti modular necks and can lead to release of metal ions and debris resulting in local soft-tissue destruction [ 23 , 24 , 25 , 26 , 27 ]. Even though no formal data of ALTRs were found in the patients’ records, the higher revision rates of DM stem THA system because of aseptic loosening may be the consequence of additional modularity at the stem-neck junction.…”
Section: Discussionmentioning
confidence: 99%